Low-Density Lipoprotein Cholesterol and Mortality in Patients With Intracerebral Hemorrhage in Taiwan - Wen, Chi-Pang; Lee, Yi-Che; Sun, Yuan-Ting; Huang, Chih-Yuan; Tsai, Chon-Haw; Chen, Po-Lin; Chang, Wei-Lun; Yeh, Po-Yen; Wei, Cheng-Yu; Tsai, Ming-Jun; Sun, Yu; Lin, Chih-Hao; et al. (Frontiers in Neurology, 2022)
Objective: Lower serum low-density lipoprotein cholesterol (LDL-C) levels are associated with increased intracerebral hemorrhage (ICH) risk. However, reverse causality and residual confounding has not attracted public attention. Therefore, we assessed whether people with LDL-C have increased risk of mortality adjusting for potential confounders using two large Taiwan cohorts. Methods: The Mei-Jhao (MJ) cohort has 414,372 adults participating in a medical screening program with 378 ICH deaths within 15 years of follow-up (1994–2008). Cox proportional hazards regressions estimated hazard death ratios according to LDL-C levels. We identified 4,606 ICH patients from the Taiwan Stroke Registry (TSR) and analyzed the impact of LDL-C on 3-month mortality. Results: Low cholesterol (LDL-C <100 mg/dL), found in 1/4 of the MJ cohort, was highly prevalent (36%) among young adults (age 20–39). There was a graded relationship between cholesterol and mortality for ICH [Hazard ratio, 1.56; 95% confidence interval (CI), 1.13–2.16]. Compared with patients with an LDL-C of 110–129 mg/dL in TSR, the risk for mortality was 1.84 (95% CI, 1.28–2.63) with an LDL-C of <100 mg/dL. Conclusion: Lower serum LDL-C level independently predicts higher mortality after acute ICH. While its causative role may vary, low cholesterol may pose potential harms in Taiwan.